Problems of development of a cloud-oriented educational environment of the university - Ахметов, Бахытжан; Лахно, Валерий; Адранова, Асельхан; Касымбергебаев, Бауржан (Pedagogy and Psychology, 2020)
This article discusses the problems of ever-increasing demands on the organization and quality of the educational process on the part of society. Today there are new opportunities for the comprehensive development of students of the XXI century, new, more effective information and communication technologies (ICT), in particular cloud- oriented learning environments (COLE), are developing rapidly. The problems of the development of theoretical and methodological foundations for designing a cloud-oriented educational environment of the university and the justification of the structural scheme of its interaction with the methodological center of the ministry based on the use of cloud technologies are analyzed. It is necessary to introduce such models of the learning environment, which will allow to fully satisfy the demands of teaching staff on the organization and conduct of classes of a new type, the activation of educational activities of students, the formation of digital competence and the comprehensive development of personality. Such opportunities are provided by the use of a cloud-based educational environment of the university.